Current role of hysteroscopy in infertility - Guamán-Gualpa, William (2023)
Since the 1980s, hysteroscopy has been used for the study and treatment of fibroids, polyps, septums, intrauterine adhesions, dysfunctional and abnormal uterine bleeding and in the evaluation of the endometrium prior to embryo transfer in In Vitro Fertilization (IVF) treatments. ). The exhaustive study of the patients, the expertise of the gynecologist, the precise indication of the procedure, the correct evaluation of contraindications, the use of an adequate and careful exploratory and surgical technique, together with the correct use of technology, will make hysteroscopy a reliable method of low morbidity and no mortality.